What the radiologist should know about the role of interventional radiology in urology - Tibana,Tiago Kojun (2019)
Abstract Interventional radiology has been constantly developing in terms of the techniques, materials, and methods of intervention. It interacts with all areas of medicine, always with the ultimate goal of ensuring the well-being of patients. Advances in imaging techniques, especially in the last two decades, have led to a paradigm shift in the field of urological imaging interventions. Many urologic diseases that were previously treated only surgically can now be effectively managed using minimally invasive image-guided techniques, often with shorter hospital stays and requiring only local anesthesia or conscious sedation.